PENGARUH PENAMBAHAN TEPUNG TOMAT (Solanum lycopersicum l) TERHADAP KUALITIAS INTERNAL TELUR AYAM RAS - Timbuleng, Vrilly E.; Laihad, Jacqueline T.; Leke, Jein R.; Rimbing, Siane C (ZOOTEC, 2015)
EFFECT OF TOMATOES STARCH (Solanum lycopersicum l) ON INTERNAL EGG QUALITY OF LAYING CHICKEN. This research has been done to determine the effect of tomatoes starch on the internal egg quality of laying chicken. The material used in this study was a 100 laying hens aged 36 weeks with the following treatments P0: basal ration without tomatoes startch; P1: 98% of basal ration + 2% of tomatoes starch: P2; 96% of basal ration + 4% tomatoes starch; P3: 94% of basal ration + 6% of tomatoes starch; P4: 92% of basal ration + 8% of tomatoes starch. Research design used was the completely randomized design (CRD) with 5 treatment and 5 replications. Duncan's multiple range test was used for further test. Variables were observed during the study include egg yolk index, yolk color, and Haugh unit (HU). The results showed that the addition of tomatoes in the diet has no significant effect (P> 0.05) on egg yolk index and haugh units (HU), but highly significant effect (P <0,01) against the color of egg yolks. Based on the research results obtained, it can be concluded that the addition of tomatoes starch in ration as much as 8% will provide a good response to the effect of egg yolk index, Haug units (HU), and yellow egg of laying chicken. Keywords :Laying Chicken, Internal Egg Quality, Tomatoes Starch.